Pooled Cohort Equations and the competing risk of cardiovascular disease versus cancer: Multi-Ethnic study of atherosclerosis - Seamus P. Whelton; Catherine Handy Marshall; Miguel Cainzos-Achirica; Omar Dzaye; Roger S. Blumenthal; Khurram Nasir; Robyn L. McClelland; Michael J. Blaha (Elsevier, 2021)
Background: many of the modifiable variables in the Pooled Cohort Equations (PCE) are shared risk factors for cardiovascular disease (CVD) and cancer, which are the two leading causes of death in the United States. We sought to determine the utility of the PCE risk for the synergistic risk prediction of CVD and cancer. Methods: we identified 5,773 participants (61.5 years and 53% women) without baseline CVD or cancer from the Multi-Ethnic study of atherosclerosis. The primary outcome was time to first event of either incident CVD or incident cancer. We calculated competing risk and cause-specific hazard models to examine the association of the PCE groups (<7.5%, 7.5-<20%, ≥20%) with the competing risk of CVD and cancer. Results: the rate of incident CVD and cancer was higher with higher PCE risk, but the absolute event rate was low for both CVD and cancer when the PCE risk was <7.5%. Participants with a PCE <7.5% had a higher rate of cancer (4.8) compared to CVD (3.3) per 1000 person-years, while the rate of CVD (11.5) was higher than cancer (8.6) for PCE between 7.5 and <20%. The ratio of CVD to cancer increased in a logarithmic manner and at a PCE risk of approximately 7.2% the risk for CVD and cancer was equal. In adjusted competing risk modeling, a PCE risk of ≥20% compared to <7.5% was associated with a greater risk of both CVD [7.18 (95% CI 5.77-8.94)] and cancer [3.59 (95% CI 2.91-4.43)]. Conclusions: these findings highlight the importance of age and modifiable risk factors for CVD and cancer prevention. In addition, it suggests that the PCE can provide important information for both CVD and cancer risk stratification, which may guide a synergistic approach to screening and preventive therapies for the two leading causes of death in the United States.